Parkinson's Disease Remote Patient Monitoring During the COVID-19 Lockdown - Motolese, Francesco; Magliozzi, Alessandro; Puttini, Fiorella; Rossi, Mariagrazia; Capone, Fioravante; Karlinski, Keren; Stark-Inbar, Alit; Yekutieli, Ziv; Di Lazzaro, Vincenzo; Marano, Massimo (Frontiers in Neurology, 2020)
Objective: To evaluate the feasibility of a smartphone remote patient monitoring approach in a real-life Parkinson’s disease (PD) cohort during the Italian COVID-19 lockdown. Methods: Fifty-four non-demented PD patients who were supposed to attend the outpatient March clinic were recruited for a prospective study. All patients had a known UPDRS-III and a modified Hoehn and Yahr scale score and were provided with a smartphone application capable of providing indicators of gait, tapping, tremor, memory and executive functions. Different questionnaires exploring non-motor symptoms and quality of life were administered through phone-calls. Patients were asked to run the app at least twice per week (i.e., full compliance). Subjects have been phone-checked weekly along a 3-week period for compliance and final satisfaction questionnaires. Results: Forty-five patients (83.3%) run the app at least once; Twenty-nine (53.7%) subjects were half-compliant, while 16 (29.6%) were full compliant. Adherence was hindered by technical issues or digital illiteracy (38.7%), demotivation (24%) and health-related issues (7.4%). Ten patients (18.5%) underwent PD therapy changes. The main factors relating with compliance included loss of interest, sadness, anxiety, the presence of falls and higher Hoehn and Yahr scale. Gait, tapping, tremor and cognitive application outcomes were correlated to disease duration, UPDRS-III and H&Y. Discussion: the majority of patients were compliant and satisfied by the provided monitoring program. Some of the application outcomes were statistically correlated to clinical parameters, but further validation is required. Our pilot study suggested that the available technologies could be readily implemented also with the current population technical and intellectual resources.